Component analysis of Kazakh weapons names (based on the trilogy “Nomads” by I. Yesenberlin) (Eurasian Journal of Philology Science and Education, 2022)
For the Kazakh people, who experienced incessant wars, raids in certain historical times, and dreamed of creating a strong independent state, it was considered half the victory to have full-fledged military equipment with various types of weapons. The article is devoted to the component analysis of the names of weapons in the trilogy “Nomads” by the outstanding historian and writer I. Esenberlin. In times of war, invasions, when the head of the people does not rise from the enemy, the dream of the people is to pull out one arm, one bank to become a sovereign country, the heroes of the Khan and boys spoke in their works, a unique son of the Kazakh I. Yesenberlin. He wrote a work on the history and literature of the Kazakh people and gave it the name “Nomads”.This study provides semantic analysis based on the lexical breakdown of words, suggesting that their semantic interactions are systematically given meaning. Semantic analysis of fictional text allows the reader to create a line of communication between terms and names and to establish meanings that are not available for other semantic theories. As a research concept, we presented the results of the component analysis of the names of weapons in the form of a diagram with a percentage.